Implementasi Konsep Editing Pop Culture pada Program Video On Demand Politichoose Narasi TV - Sigit Rizal Hidayat; Citra Dewi Utami (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2023)
Video on Demand is a term for presenting videos that can be accessed online by streaming or offline by downloading. Video on demand gives control to its users where they have the freedom to choose what they want to watch without being bound by a certain time and place and can repeat the show as long as they are still connected to the internet. One digital media company that produces a lot of video on demand programs is Narasi TV. This journal will discuss the concept of editing pop culture program video on demand Politichoose Narasi TV. The Pop Culture editing concept in general is an editing technique with a modern style, following trends, dynamic, and widely followed by other people so that it can attract a wider audience, especially the younger generation, who are the main target of the politicoose program. There are three episodes, including an episode discussing one of the majors, an episode discussing sexual violence in educational institutions and an episode discussing medical waste.